Contrasting weight changes with LY2605541, a novel long‐acting insulin, and insulin glargine despite similar improved glycaemic control in T1DM and T2DM1. Issue 4 (31st October 2013) - Jacober, S. J.; Rosenstock, J.; Bergenstal, R. M.; Prince, M. J.; Qu, Y.; Beals, J. M.
<x xml:space="preserve">Abstract</x> Aims The basal insulin analogue LY2605541, a PEGylated insulin lispro with prolonged duration of action, was previously shown to be associated with modest weight loss in Phase 2, randomized, open‐label trials in type 2 (N = 288) and type 1 (N = 137) diabetes mellitus (T2DM and T1DM), compared with modest weight gain with insulin glargine. Exploratory analyses were conducted to further characterize these findings. Methods Pearson correlations between change in body weight and other variables were calculated. Continuous variables were analysed using a mixed linear model with repeated measurements. Proportions of subjects with weight loss were analysed using Fisher's exact test for T2DM and Nagelkerke's method for T1DM. Results Weight loss was more common in LY2605541‐treated patients than in patients treated with insulin glargine (T2DM: 56.9 vs. 40.2%, p = 0.011; T1DM: 66.1 vs. 40.3%, p < 0.001). More LY2605541‐treated patients experienced ≥5% weight loss compared to patients treated with glargine (T2DM: 4.8 vs. 0%, p = 0.033; T1DM: 11.9 vs. 0.8%, p < 0.001). In both the T1DM and T2DM studies, weight change did not correlate with baseline body mass index (BMI), or change in HDL‐cholesterol in either treatment group. No consistent correlations were found across both studies between weight change and any of the variables assessed; however, weight change was significantly correlated with hypoglycaemia rate in glargine‐treated T2DM patients. Conclusion In two Phase 2 trials, improved glycaemic control with long‐acting basal insulin analogue LY2605541 is associated with weight loss in previously insulin‐treated patients. This weight change is independent of baseline BMI or hypoglycaemia.